2013
DOI: 10.1073/pnas.1211776110
|View full text |Cite
|
Sign up to set email alerts
|

Metallothioneins negatively regulate IL-27–induced type 1 regulatory T-cell differentiation

Abstract: IL-27–induced type 1 regulatory T (Tr1) cells suppress autoimmunity by producing IL-10. Signal transducer and activator of transcription (STAT) 1 and STAT3 have been described as key transcription factors that promote IL-10 secretion from Tr1 cells induced by IL-27. However, the molecular pathways for negatively regulating Tr1 cell differentiation remain elusive. Here, we show that IL-27 induces metallothioneins (MTs) that in turn prevent Tr1 cell development. MT expression leads to the reduction of STAT1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 30 publications
(31 reference statements)
1
61
1
Order By: Relevance
“…Although studies were previously performed in T cells, Mt1/Mt2-deficient mice were found to produce increased levels of Il10 following an immune challenge with anti-CD3/CD28. 59 Still, the role of metallothionein genes during immune challenges and inflammation are not fully elucidated, and low expression of Mt1 supports the proinflammatory nature of the response at the measured time-point. 60 Direct association in the literature between macrophages and the underexpressed gene Ptprcap was less clear, although it has been found in the monocyte precursors to macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…Although studies were previously performed in T cells, Mt1/Mt2-deficient mice were found to produce increased levels of Il10 following an immune challenge with anti-CD3/CD28. 59 Still, the role of metallothionein genes during immune challenges and inflammation are not fully elucidated, and low expression of Mt1 supports the proinflammatory nature of the response at the measured time-point. 60 Direct association in the literature between macrophages and the underexpressed gene Ptprcap was less clear, although it has been found in the monocyte precursors to macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…MTs play diverse roles in metal detoxification, antioxidation, regulation of Zn 2+ -dependent proteins, immune defence and cell differentiation 29 30. Notably, MTs regulate cellular Zn 2+ levels, and impaired Zn 2+ homoeostasis is implicated in the pathophysiology of aging and various diseases 31 32.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both STAT1 and STAT3 are involved in IL-10 production ( Figure 3 ). In contrast to the positive regulators, metallothioneins can inhibit Tr1 generation by inhibiting phosphorylation of STAT1 and STAT3 [53]. Besides increasing the production of IL-10 by Tr1, IL-27 can induce IL-10 production in other activated T cell subsets, including Th1, Th2, Th17, and Treg [13, 50, 54].…”
Section: Influence Of Il-27 On T Cells and B Cellsmentioning
confidence: 99%